Pelatihan Pembukuan Dalam Penjurnalan Dengan Sistem Digital di Desa Sanehen Kabupaten Aceh Tengah - Surahman, Bambang; Putra, Erwinsyah; Nituah, Mude Teger; Munawirsyah, Munawirsyah; Irsan, M.; Arafah, Nike Tarlo; Olawati, Olawati; Pariandi, Pariandi; Putrina, Putrina; Sedikentara, Rozan; Mahbengi, Sinta Gusti; Evtaria, Sumarni; Putri, Tasya Amelia; Khairunnisa, Khairunnisa; Rahmiati, Mita; Imanullah, Zaid (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Training in Digital Accounting Journalization in Sanehen Village, Central Aceh Regency: Integration with Thematic Real Work Lecture (KKNT). This research explains the implementation of digital accounting training in Sanehen Village, Central Aceh Regency, as part of the Thematic Real Work Lecture (KKNT) activities. The research aims to enhance the local community's capacity in accounting and journalization through digital technology. The research method involves active collaboration with village stakeholders and the integration of training into KKNT. The training results show an improvement in understanding and efficiency in using digital systems. In the context of KKNT, this training has a positive impact on community development, increasing participants' involvement in sustainable village development. The discussion includes concrete benefits of KKNT integration and challenges faced. In conclusion, digital accounting training not only enhances financial literacy but also contributes to the goals of village development within the KKNT framework. This study provides guidance for similar programs in rural areas facing similar challenges.